The physiology of sprouting and its ecological implications for Savanna woodland and dynamics in the Nylsvley Nature Reserve, Limpopo Province, South Africa - Ligavha-Mbelengwa, Maanda Hadzhi (My University, 2024)
Disturbance in its various forms is an integral component of any ecosystem, and it contributes significantly to the patterning of the vegetation. Many savanna plant species survive disturbance, such as cutting or clipping, through resprouting. Sprouting is important, particularly in situations where chances for the establishment of seedlings is rare. High disturbance intensity suppresses plant recovery, while low disturbance intensity stimulates plant regrowth. Disturbing plants frequently depletes stored carbohydrate reserves which are indispensable for regrowth, while disturbing plants less frequently allows plants space to accumulate root carbohydrate reserves. Savanna plants in game reserves are usually exposed to disturbance in the form of grazing, browsing, accidental fires, and competition. It is necessary to comprehend how savanna plant species respond to the disturbance for the sustenance of the life of the game in those ecosystems. This study assessed how savanna plants (i) respond to cutting, (ii) relate to bark thickness, stem diameter, and fire, and (iii) respond to release from competition. Chapter 3 of the current thesis experimented on juveniles of the two savanna plant species, namely Dichrostachys cinerea (D. cinerea) and Terminalia sericea (T. sericea), and Chapter 4 experimented on seedlings and juveniles of the same two savanna plant species referred to in chapter 3. Juvenile individuals that were utilized for experimentation in chapter 3 were not the same as those utilized in Chapter 4. Dichrostachys cinerea (D. cinerea) and Terminalia sericea (T. sericea), were subjected to clipping. In one instance, a group of juvenile plants per species was cut seasonally during the first year of experimentation for the whole experimental period, while in another instance, seedlings and juveniles were cut; the responses of plants were monitored and compared in both instances. Clipping of individual plant species monthly in the year simulated how seasons differentially affect plants' responses to cutting. The study was carried out for two and half years. The heights of cut plants were compared to establish how the plants responded to clipping. The heights of the plants were measured in both instances only towards the conclusion of the experiments. The bark thickness, and stem diameter of plants of different age groups were measured using Vernier callipers and diameter tapes, respectively. Gaps created between grass plants were measured pre- and post-removal of their potential competitors. All the individual plant species that were clipped anyhow survived clipping throughout the experimental period. Winter-clipped plant species generally outgrew plants that were clipped in other seasons, probably due to ample carbohydrate root reserves during this season of the year. Juveniles grew faster than seedlings in terms of height when both were cut at the same time of the day, presumptively due to more carbohydrates in their roots than in those of the seedlings. More seedlings died than juveniles when both were exposed to the same fire intensity. We found root reserves affected differentially between seasons of the year. The bark thickness increased with plant age and height to about 50 cm in trunk circumference; thereafter, the relationship was inconsistent. Openings that resulted when grass plants competed for resources such as moisture became readily available for invasion by new plant species, mainly alien plants. Managed disturbance is thus important and necessary to maintain ecosystems in balance. Communities should thus be educated on how savanna ecosystems respond to disturbances at different seasons of the year to mitigate situations where our savanna ecosystems could be converted into ecosystems that are not suitable for savanna games.
Ph.D. (Biological Sciences)
Department of Biological Sciences
Keywords: UCTD; 577.48096825; Savannas -- South Africa -- Limpopo; Grasslands -- South Africa -- Limpopo; Plains -- South Africa -- Limpopo; Nylsvley Nature Reserve (South Africa)